Optimum Commodity Taxation with a Non-Renewable Resource - Julien Daubanes; Pierre Lasserre (ETH Zurich, CER-ETH - Center of Economic Research, 2011)
Optimum commodity taxation theory asks how to raise a given amount of tax revenue while minimizing distortions. We reexamine Ramsey's inverse elasticity rule in presence of Hotelling-type non-renewable natural resources. Under standard assumptions borrowed from the non-renewable-resource-extraction and from the optimum-commodity-taxation literatures, a non-renewable resource should be taxed in priority whatever its demand elasticity and whatever the demand elasticity of regular commodities. It should also be taxed at a higher rate than other commodities having the same demand elasticity and, while the tax on regular commodities should be constant, the resource tax should vary over time. There are two basic ways to alleviate resource supply limitations; one is to produce reserves for subsequent extraction; the other one is to rely on imports. When the generation of reserves by exploration is determined by the net-of-tax rents derived during the extraction phase, reserves become a conventional form of capital and royalties tax its income; our results contradict Chamley's conclusion that capital should not be taxed at all in the very long run. When the economy is autarkic, in the absence of any subsidy to reserve discoveries, the optimal tax rate on extraction obeys an inverse elasticity rule almost identical to that of a commodity whose supply is perfectly elastic. As a matter of fact, there is a continuum of optimal combinations of reserve subsidies and extraction taxes, irrespective of whether taxes are applied on consumption or on production. When the government cannot commit, extraction rents are completely expropriated and subsidies are maximum. In general the optimum Ramsey tax not only causes a distortion of the extraction path, as happens when reserves are given, but also distorts the level of reserves developed for extraction. When that distortion is the sole effect of the tax, it is determined by a rule reminiscent of the inverse elasticity rule applying to elastically-supplied commodities. In an open economy, Ramsey taxes further acquire an optimum-tariff dimension, capturing foreign resource rents. For countries that import the resource, the result that domestic resource consumption is to be taxed at a higher rate than conventional commodities having the same demand elasticity emerges reinforced.
Keywords: Q31; Q38; H21; 330; Optimum commodity taxation; Inverse elasticity rule; Non-renewable resources; Hotelling resource; Supply elasticity; Demand elasticity; Capital income taxation; Verbrauchsteuer; Optimale Besteuerung; Erschöpfbare Ressourcen; Hotelling-Regel; Preiselastizität; Kapitalertragsteuer; Theorie